Recent Advances in Transition Metal-Catalyzed Ring-Opening Reaction of Aziridine - Partha Sarathi Bera; Yafia Kousin Mirza; Tarunika Sachdeva; Milan Bera (Compounds)
The smallest strained, saturated N-heterocycles, such as aziridine, can be a valuable building block in synthetic organic chemistry. Ring-opening reactions with various nucleophiles could be the most important strategy to synthesize various value-added molecular entities. Therefore, regioselective ring-opening reactions of aziridines with various heteroatomic nucleophiles and carbon nucleophiles establish a useful synthetic methodology to synthesize biologically relevant β-functionalized alkylamines. The regio-selective ring-opening of aziridines is highly dependent on the substrate combination, and stereochemical control is challenging for Lewis acid-promoted reactions. Therefore, the development of a robust, catalytic ring-opening process that assists in the accurate prediction of regioselectivity and stereochemistry is highly desirable. Consequently, a large number of publications detailing distinct methods for aziridine ring-opening reactions can be found in the literature. In this review, we discuss several transition metal catalyzed cross-coupling reaction protocols for the ring opening of substituted aziridines with various carbon nucleophiles.